2013
DOI: 10.1155/2013/806025
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Molecules Involved in Regulatory T-Cells Induction by Dendritic Cells in Cancer?

Abstract: Dendritic cells (DCs) are essential for the maintenance of homeostasis in the organism, and they do that by modulating lymphocyte priming, expansion, and response patterns according to signals they receive from the environment. The induction of suppressive lymphocytes by DCs is essential to hinder the development of autoimmune diseases but can be reverted against homeostasis when in the context of neoplasia. In this setting, the induction of suppressive or regulatory T cells contributes to the establishment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 101 publications
3
18
1
4
Order By: Relevance
“…In addition, the effects of DCs on Treg cell induction and expansion appear to be dependent on PD‐L1, concurrent with the present results, wherein CpG ODN and neurosphere lysate stimulation drastically upregulated PD‐L1 on DCs, and after the combinatorial administration of anti‐PD‐L1 mAb and STDENVANT, the percentage of Foxp3 + CD4 + Treg cells decreased (Fig. c ).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the effects of DCs on Treg cell induction and expansion appear to be dependent on PD‐L1, concurrent with the present results, wherein CpG ODN and neurosphere lysate stimulation drastically upregulated PD‐L1 on DCs, and after the combinatorial administration of anti‐PD‐L1 mAb and STDENVANT, the percentage of Foxp3 + CD4 + Treg cells decreased (Fig. c ).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, our data demonstrated that Inhα -/- mBMDCs induced poor allogeneic T cell responses, possibly as a consequence of lower levels of MHCII and CD86 expression and increased PD-L1 expression. In this context, PD-L1 has been shown to down regulate T cell receptor (TCR) signaling by recruiting SHP-2 [36] and consequently, promotes T cell anergy and Treg induction [37,38]. Whether the impaired maturation of Inhα -/- BMDCs has an impact on T cell polarization and Treg induction remains unclear and is currently being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…38 Involved in the negative regulation of adaptive responses, 39 PD-1/PD-L1 pathway was first studied. The results indicated that the inhibition of DC maturation, the release of a tolerogenic cytokine profile (IL-12 low IL-10 high ) and the induction of Treg cells by DC committed by genital SCC cell lines could be partially mediated by RANKL.…”
Section: Discussionmentioning
confidence: 99%